Regulation of marriage and family relations by the bolshovs in the territory of Ukraine in 1917-1926 - Kozar, Yurii; Lazariev , Viktor; Oleksenko, Roman; Kliuienko, Eduard; Babak, Oksana (Interacción y Perspectiva, 2023)
The study aims to review the regulation or marriage and family relations by the Bolsheviks in Ukraine in 1917-1926. With the coming to power of the Bolsheviks, a system of legislation that governs marriage and family relations began to be created. At the regulatory level, the legal consequences of divorce were recognized and a number of guarantees were defined for women and children. The Ukrainian church, unlike the church of the RSFSR, was not immediately separated from the state. Still, only a search was made for specific relations between it and the power structures, in which the question of the state significance of church acts was also raised. The decisions being prepared by state bodies and those that had already been adopted were supposed to free the church from purely civil functions gradually. This required a long-term evolution of the church consciousness of the laity and the clergy. During the 1920s, the institution of marriage and family relations was established, which was accompanied by reforms in the family sphere. An essential role in the formation of a new approach to marriage and family relations of the "new model" was played by stable traditions of family formation